The geology, ecology, and human history of the San Luis Valley - Beeton, Jared Maxwell, editor; Saenz, Charles Nicholas, editor; Waddell, Benjamin James, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2020)
Explores the rich landscapes and diverse social histories of the San Luis Valley, an impressive mountain valley spanning over 9,000 square miles that crosses the border of south-central Colorado and north-central New Mexico. Contributors uncover the natural and cultural history of the region.--Provided by publisher.
Keywords: Geology -- San Luis Valley (Colo. and N.M.); Ecology -- San Luis Valley (Colo. and N.M.); Natural history -- San Luis Valley (Colo. and N.M.); San Luis Valley (Colo. and N.M.) -- History